Biological efficacy of a 600 mg loading dose of clopidogrel in ST-elevation myocardial infarction - Bonello, Laurent; Berbis, Julie; Laine, Marc; Armero, Sébastien; Bessereau, Jacques; Jacquin, Laurent; Bonello, Caroline; Camillieri, Elise; Barragan, Paul; Dignat-George, Françoise; Paganelli, Franck; Camoin-Jau, Laurence (Thrombosis and Haemostasis, 2012)
Optimal platelet reactivity (PR) inhibition is critical to prevent thrombotic events in primary percutaneous coronary intervention (PCI). We aimed to determine the relationship between high on-treatment platelet reactivity (HTPR) and ST-elevation myocardial infarction (STEMI) following a 600 mg loading dose (LD) of clopidogrel. We performed a prospective monocentre study enrolling patients on clopidogrel undergoing PCI. The VASP index was used to assess PR inhibition after clopidogrel LD. HTPR was defined according to the consensus as a VASP index ≥50%. The present study included 833 patients undergoing PCI. Most patients had PCI for an acute coronary syndrome (58.7%). The mean VASP index was 50 ± 23% with a large inter-individual variability (range: 1–94%). Patients with a VASP index ≥50% were significantly older (p= 0.03), with a higher body mass index (BMI) (p<0.001), more often diabetic (p=0.03), taking omeprazole (p=0.03), admitted for an acute coronary syndrome (ACS) and with a high fibrinogen level compared to good responders (VASP <50%). In multivariate analysis BMI, omeprazole use, ACS and high fibrinogen level (p<0.001) remained significantly associated with HTPR. Of importance, in this analysis STEMI was independently associated with HTPR when compared with the other forms of ACS (NSTEMI and unstable angina) with an odd ratio of 2.14 (95% CI: 1.3 –3.5; p=0.003). In conclusion, STEMI is associated with high on-treatment platelet reactivity following 600 mg of clopidogrel. The present results suggest that 600 mg of clopidogrel may not be able to achieve an optimal PR inhibition in STEMI patients undergoing PCI and more potent drugs may be preferred.
Keywords: VASP index; percutaneous coronary intervention; high on-treatment platelet reactivity; acute coronary syndrome